Prinsip Menjaga Hubungan Baik dengan Pelanggan pada Manajemen Mutu Terpadu dalam Perspektif Islam: The Principle of Maintaining Good Relationships with Customers in Total Quality Management from an Islamic Perspective - Muhammad Hamka; Maemuna Sa'diyah; Agusman, Agusman (Litera Academica Publishing, 2024)
The principle of maintaining good relationships with customers is a key aspect of achieving business success. This article examines the application of this principle within the framework of Total Quality Management (TQM) from an Islamic perspective. The article aims to bridge modern management practices with Islamic teachings, providing insights into how TQM principles can be effectively implemented while adhering to Islamic values. This study employs a qualitative methodology through literature review and case study analysis. The findings indicate that Islamic teachings, particularly related to honesty, fairness, and trustworthiness, align with the TQM approach to customer relationship management. The application of Islamic ethics in TQM is found to strengthen business strategies in building sustainable, trust-based relationships. In conclusion, the integration of Islamic principles with TQM practices has the potential to enrich customer management approaches, fostering stronger long-term relationships. This research contributes to the development of a management model that integrates Islamic ethics with TQM, relevant for companies seeking to operate in accordance with Islamic values. The implications of this study suggest that businesses adopting this approach can achieve higher customer satisfaction and create a broader positive impact on both society and the business sector.